2014
DOI: 10.1016/j.jacc.2013.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) for Risk Assessment in Patients With Established Coronary Artery Disease

Abstract: Objectives To assess the prognostic utility of lipoprotein (a) [Lp(a)] in individuals with coronary artery disease (CAD). Background Data regarding an association between Lp(a) and cardiovascular (CV) risk in secondary prevention populations are sparse. Methods Plasma Lp(a) was measured in 6762 subjects with CAD from three studies; data were then combined with eight previously published studies for a total of 18,979 subjects. Results Across the three studies, increasing levels of Lp(a) were not associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(125 citation statements)
references
References 46 publications
7
108
1
3
Order By: Relevance
“…11 On the other hand, statins, which cause an upregulation of the LDL-receptor markedly decrease levels of LDL-cholesterol but not Lp(a). Even the opposite might be the case as already suggested a long time ago by Kostner et al 12 and very recently by O'Donoghue et al 10 : both studies observed an increase in Lp(a) concentrations after successful lowering of LDL-cholesterol by statins. This is in line with the results of the JUPITER Study in the present issue of Circulation 8 : patients under rosuvastatin treatment showed even a statistically significant positive shift in the overall Lp(a) distribution that was not observed in the placebo group.…”
Section: February 11 2014mentioning
confidence: 80%
See 1 more Smart Citation
“…11 On the other hand, statins, which cause an upregulation of the LDL-receptor markedly decrease levels of LDL-cholesterol but not Lp(a). Even the opposite might be the case as already suggested a long time ago by Kostner et al 12 and very recently by O'Donoghue et al 10 : both studies observed an increase in Lp(a) concentrations after successful lowering of LDL-cholesterol by statins. This is in line with the results of the JUPITER Study in the present issue of Circulation 8 : patients under rosuvastatin treatment showed even a statistically significant positive shift in the overall Lp(a) distribution that was not observed in the placebo group.…”
Section: February 11 2014mentioning
confidence: 80%
“…However, the findings of a similar association of Lp(a) with CVD events independently of the LDL-cholesterol values are in contrast to a very recently published meta-analysis of secondary prevention studies that observed an effect modification by LDL-cholesterol: the association between Lp(a) concentrations and CVD events was only observed in studies in which the average LDL-cholesterol was ≥130 mg/dL at baseline and not in those below this value. 10 A pronounced heterogeneity in the study populations, inclusion criteria, therapeutic regimens, and duration of observation periods might have contributed to the differences in results between the hitherto published studies.…”
Section: Article See P 635mentioning
confidence: 99%
“…The most robust data to date regarding the interaction of Lp(a) and LDL‐C originate from the Women's Health Study (n=27 791 women with 899 incident cardiovascular events) in which a strong interaction between elevated Lp(a) levels (>44 mg/dL) and high LDL‐C levels (>3.1 mmol/L) was observed in women 24. Finally, although a recent observational study has suggested that patients with ACS and high Lp(a) have recurrent cardiovascular events despite low LDL‐C,25 a recent large meta‐analysis of statin trials in secondary prevention suggested that Lp(a) was only predictive of recurrent events in individuals with high LDL‐C >3.4 mmol/L 26. Although these studies have all demonstrated some evidence for interaction between elevated Lp(a) and LDL‐C levels, these analyses have been limited by small sample sizes, the lack of formal interaction tests, the inclusion of only women or the use of surrogate end points (ie, angina or vascular imaging).…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that common cut points and valid comparisons of Lp(a) levels among laboratories is not feasible at this point in time because of substantial differences in Lp(a) methods and calibrations and differences among both men and women (30)(31)(32)(33). Meta-analysis of long-term prospective studies were performed to assess the relationship of Lp(a) concentration with risk of major vascular and nonvascular outcomes.…”
Section: Lp(a) Levels For Defi Nition Of Cvd Riskmentioning
confidence: 99%